Common Ancestor and Genetic Diversity in Penna Model (Communications in Computational Physics, 2010)
The characteristic of individual is described by the Penna model. Based oninformation entropy and the Penna model we define the entropy in the Penna modelto discuss common ancestors and genetic diversity for two reproduction modes withand without mutation. About the problem of common ancestor, we find that all livingindividuals at any time step have a set of common ancestors which belongs to differenttimes. They have the most recent common ancestor and earlier common ancestors.The analysis of genetic diversity shows that the complexity of ecosystems is caused bymutations and there is no contribution of sexual reproduction to conserving geneticdiversity at long time scales. Moreover, in stable environment genetic diversity inasexual reproduction mode is higher than that in the sexual case.